Der Weg nach Mekka – Die Reise des Muhammad Assad - Misch, Georg (Austria, 2008)
In the early 1920s Leopold Weiss, a Viennese Jew, travelled to the Middle East. The desert fascinated him, and Islam became his new spiritual home. He left his Jewish roots behind, converted to Islam and changed his name to Muhammad Asad. He became one of the most important Muslims of the 20th century, first as an advisor at the royal court of Saudi Arabia, and later translating the Koran into English. Asad was also a co-founder of Pakistan and its ambassador to the UN. The director follows his fading footsteps, leading from the Arabian desert to Ground Zero. He finds a man who was not looking for adventures but rather wanted to act as a mediator between East and West. A Road To Mecca takes this opportunity to deal with a heated debate on the nature of Islam and its role in today’s world.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films